A critical reconceptualization of faculty readiness for online teaching. Issue 3 (2nd July 2020) - Cutri, Ramona Maile; Mena, Juanjo
ABSTRACT: Online courses are mainstream throughout higher education. This pattern has been accelerated, temporarily or permanently, due to the coronavirus pandemic (Allen & Seaman, 2016; Arum & Stevens, 2020; Garrison, 2011). Tenure-track and contingent faculty's willingness to teach online serves students, but little research critiques the forces that produce and constrain faculty's efforts. Even the most current discussions of faculty readiness lack a strong grounding in criticality. Without such a critical orientation, the power and equity issues involved in the higher education marketplace of online teaching cannot be adequately examined. This critical integrated literature review of 44 studies documents themes of the affective dimensions and identity disruption surrounding faculty's readiness to teach online and explores their professional vulnerability. Structural and cultural forces that produce and constrain faculty's experiences transitioning to online teaching emerged from the analysis. This conceptualization of faculty readiness provides a foundation upon which to theorize faculty's equitable experiences of online teaching.